The Impact of Partnerships and Information Sharing on Corporate Sustainable Performance: A Mediation Model Moderated by Government Support - Yue, Longfei; Ye, Meng; Chen, Qing (Frontiers in Psychology, 2022)
Based on the theory of strategic alliances and social networks, this paper empirically studies the relationship between partnership, information sharing and sustainable performance through a questionnaire survey of Chinese sports equipment manufacturers. The findings show that partnerships have a positive impact on sustainable performance; that information sharing plays a role in mediating the relationships between trust, cooperation and sustainable performance; and that government support can positively impact the effect of partnerships on sustainable performance. Through empirical research, this paper proves the mechanism of the impact of partnership on alliance performance, further expands the theoretical basis for enterprises’ establishment of strategic alliances, and has important enlightening significance for enterprises within alliances aiming to rationally use the networks inside and outside their alliances to obtain knowledge and resources and improve their sustainable performance.